1997
DOI: 10.1038/sj.bmt.1700979
|View full text |Cite
|
Sign up to set email alerts
|

Autologous peripheral blood stem cell transplantation for acute myelogenous leukemia

Abstract: Summary:with acute myelogenous leukemia (AML). 1,2 However, most will relapse despite consolidation and maintenance chemotherapy. Therefore, post-remission therapy is one of The safety and efficacy of myeloablative therapy followed by autologous peripheral blood stem cell transthe most important issues in the treatment of AML. An increasing number of AML patients have been treated with plantation (ABSCT) for acute myelogenous leukemia (AML) were evaluated in 60 patients. Peripheral blood intensified consolidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 6 publications
4
39
1
1
Order By: Relevance
“…It is now well proven that hemopoiesis recovery (engraftment) is more rapid with PBSCT than with BMSCT [11][12][13]. The most important factor for hemopoietic recovery after ASCT is the dose of progenitor cells infused [11][12][13]. In our study the engraftment after PBSCT was significantly shorter than after BMSCT by 11 days (for neutrophils recovery) and by 37 days (for platelets recovery), and it was comparable with other series.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is now well proven that hemopoiesis recovery (engraftment) is more rapid with PBSCT than with BMSCT [11][12][13]. The most important factor for hemopoietic recovery after ASCT is the dose of progenitor cells infused [11][12][13]. In our study the engraftment after PBSCT was significantly shorter than after BMSCT by 11 days (for neutrophils recovery) and by 37 days (for platelets recovery), and it was comparable with other series.…”
Section: Discussionsupporting
confidence: 75%
“…It is now well proven that hemopoiesis recovery (engraftment) is more rapid with PBSCT than with BMSCT [11][12][13]. The most important factor for hemopoietic recovery after ASCT is the dose of progenitor cells infused [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Sanz et al reported fatal VOD in 2 of 24 patients who received a fixed dose of BU (16 mg/kg) and cyclophosphamide (CY, 200 mg/kg) followed by auto-PBSCT for AML [19]. As reported previously, we found no TRM among 60 AML patients treated with a fixed dose of the G-CSF-combined-BEA regimen, and only 2 patients developed hepatic toxicity greater than grade 2; however, early severe hepatic toxicity developed in 1 patient who was autografted in second remission [16]. Thus, in patients who have a high risk of TRM, e.g., patients with advanced stages or those receiving multiple courses of transplantation, adjustment of the targeting dose of BU may be helpful to avoid severe RRT even in the setting of autologous transplantation.…”
Section: Discussionsupporting
confidence: 80%
“…The patient was treated with a pre-transplant conditioning regimen consisting of BU 0.8 mg/kg orally every 6 hr on days À8 to À5, etoposide 20 mg/kg iv on days À4 and À3, CA 100 mg/m 2 continuous iv on days À12 to À5, CA 3 g/m 2 iv every 12 hr on days À4 and À3, and G-CSF at a dose of 5 mg/kg on days À14 to À8 and 10 mg/kg on days À7 to À4 as described previously [16]. To provide the accurate assessment of BU plasma levels during conditioning, blood samples were collected at 2 and 6 hr on days À7 and À6 of BU administration.…”
Section: Case Reportmentioning
confidence: 99%
“…The safety and efficacy of this regimen for the treatment of AML were evaluated previously, 5,6 and the administration of G-CSF enhanced the efficacy of chemotherapy in patients with AML. 7 After the conditioning chemotherapy, peripheral blood stem cells were reinfused.…”
Section: B Cmentioning
confidence: 99%